The Influence Of Product Quality, Product Design, And Product Variation On Product Innovation In The Store Sm Binjai Bed Sheets - Intan Diah Lucky; Dian Septiana Sari; Roro Rian Agustin (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the effect of product quality, product design, and product variation on product innovation at the Sm Sprei Binjai Store. This study used a quantitative method involving 67 respondents. Data collection was carried out using questionnaires. The data obtained were analyzed using statistical formulas, namely by using the normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression analysis with the SPSS Version 23.0 program. The results of this study indicate that t-test, the calculated t value is 10.820, which is greater than the t-table of 1.99 with a significance level of 0.000. Thus, H1 is accepted and H0 is rejected, which means that product quality has a positive and partially significant influence on product innovation. The results of the t-test obtained a calculated t value of 2.918, which is greater than the t-table of 1.99 with a significance level of 0.005. Thus, H2 is accepted and H0 is rejected, which means that product design has a positive and partially significant influence on product innovation. The results of the t-test obtained a calculated t value of -0.208, which is smaller than the t-table of 1.99 with a significance level of 0.836. Thus, H3 is rejected and H0 is accepted, which means that product variation does not have a partially significant influence on product innovation. The results of the simultaneous test of the F count value are 82.043 with a significance level of 0.000, so it can be concluded that simultaneously the variables of product quality, product design and product variation have a significant influence on the dependent variable, namely product innovation.